Creative Thinking for the Design of Memorable Learning Experiences - Palencia Triana, César Augusto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Designing learning experiences became the great challenge for educators in many parts of the Colombian geography as well as in other countries, and that, in addition to meeting the contents required by the curricular plans, were memorable or conducive to anchoring gratification in the students. This is why the following document aims to present the characteristics of the model that has been called DEMA – Design of Memorable Learning Experiences as a contribution and reflection of both analogue and digital educational practices that are built in educational contexts.